CERITA SEBAGAI MEDIUM MEMBANGUN NILAI-NILAI KARAKTER DI SEKOLAH TAMAN KANAK-KANAK ANNIZOMIYAH PEJATEN JAKARTA SELATAN - Dwi Kartikawati (Universitas Lancang Kuning, 2019)
National character development has never been this urgent due to the rapid development of science and technology as well as globalization nowadays. This effort can be done through storytelling since it is an effective way of the instillation of morality and character development for children of a young age. Animal-themed storytelling activities in Annizomiyah Kindergarten located in Pejaten, South Jakarta, aimed to encourage students to acquire, master and comprehend the noble values in the stories such as honesty, cooperation, etc. Storytelling was one among their other various learning tools in respect of developing national characters. One of the evaluation results of these activities was that the students demonstrated high enthusiasm and abilities to interact with the storytellers. Furthermore, they were also able to answer questions regarding the stories and provided examples in their daily lives. These aforementioned activities had also improved their verbal communication abilities through a question and answer session. In conclusion, interactive storytelling is an effective way to obtain the goals of this school in regards to the character development since noble values can easily be instilled in young children’s mind through interesting and compelling stories so that they will grow as individuals with good moral characters. Kewyword: Storytelling, Character